Transparent OLEDs: Blur‐Free Outcoupling Enhancement in Transparent Organic Light Emitting Diodes: A Nanostructure Extracting Surface Plasmon Modes (Advanced Optical Materials 10/2013). Issue 10 (17th October 2013) - Choi, Chung Sock; Kim, Dong‐Young; Lee, Sung‐Min; Lim, Myung Sub; Choi, Kyung Cheol; Cho, Hyunsu; Koh, Tae‐Wook; Yoo, Seunghyup
<x xml:space="preserve">Abstract</x> On page 687, K. C. Choi and co‐workers demonstrate a nanostructured transparent organic lightemitting diode. The diode structure, with a periodically perforated layer of tungsten trioxide at the base, strongly couples the waveguide modes to the surface plasmon mode. This coupling is enhanced without any noticable effect on the transparency of the diode, meaning that this technology could be used in transparent displays with reducing the sharpness of the image. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>